Three new species of the Merodon nigritarsis group (Diptera: Syrphidae) from the Middle East - Vujić, Ante; Radenković, Snežana; Likov, Laura; Trifunov, Sonja; Nikolić, Tijana (Zootaxa, 2013)
Descriptions are given of three new species of Merodon Meigen (Diptera: Syrphidae) in the nigritarsis species group from the Middle East: Merodon angustus Vujić et Radenković n. sp., Merodon hakkariensis Vujić et Radenković n. sp. and Merodon quadraticus Vujić et Radenković n. sp. In addition, diagnostic characters are given for the nigritarsis group and distribution maps are presented for the new species and closely related taxa.